ULAMA, EDUCATION, PUBLIC SPHERE, AND LOCAL TOLERANCE IN LANGSA ACEH - Siregar, Mustamar Iqbal; Juliandi, Budi (Journal of Contemporary Islam and Muslim Societies, 2023)
Abstract: This article reviews the perspectives of ulama in shaping the locality of tolerance in the public sphere of education in Langsa, Aceh by highlighting the fact that there is local tolerance as a critical argument against the hegemony of the universal meaning of tolerance. Using a qualitative methodology, this article explores the perspective of scholars regarding the limits of tolerance such as clothing, social interaction, religious and organizational activities, and the right to receive religious education among non-Muslim students and students. This study produced several findings, first, the way to treat diversity in the Langsa-Aceh public education space is distinctive because the ulama's perspective on tolerance presents local practice both in terms of dress styles, religious and organizational activism, and religious education. Second, the perspective of these scholars reconstructs the meaning of tolerance which was originally universal in a direction that is local and contextual.Keywords: Ulama, Locality, Tolerance, Education, Aceh